Yield Mapping Hardware Components for Grains and Cotton Using On-the-Go Monitoring Systems - Rebecca Barocco; Won Suk Daniel Lee; Garret Hortman (EDIS, 2017)
This 12-page fact sheet discusses yield mapping benefits, grain yield flow sensors, grain moisture sensors, cotton yield flow sensors, differential GNSS receivers, ground speed sensors, header position sensors, computer displays, yield calculation and calibration, and costs of yield mapping hardware components.